Fibrinogen Level and Bleeding Risk During Catheter-Directed Thrombolysis Using Tissue Plasminogen Activator. (October 2015) - Lee, Kevin; Istl, Alexandra; Dubois, Luc; DeRose, Guy; Forbes, Thomas L.; Wiseman, Daniele; Mujoomdar, Amol; Kribs, Stewart; Power, Adam H.
Purpose: The purpose of this study was to determine whether low fibrinogen levels (fibrinogen level <1.5 g/L) during catheter-directed thrombolysis are associated with an increased bleeding risk. Methods: A retrospective review was performed on patients undergoing extremity arterial or venous thrombolysis between 2005 and 2013. Results: Patients in the low fibrinogen group were younger ( P = .006) and had a higher number of venous occlusive events ( P = .004). The low fibrinogen group received a larger dose of tissue plasminogen activator (tPA; P = .009) and had a longer duration of thrombolysis ( P = .010). The rates of major bleeding were not significantly different ( P = .139). Univariate analysis showed that larger total dose and longer duration of tPA infusion were associated with increased bleeding complications ( P < .01 and P = .03). Conclusion: A fibrinogen level <1.5 g/L during thrombolysis was not associated with an increased bleeding risk. However, larger dose and longer duration of thrombolysis were associated with increased bleeding risk.